2010
DOI: 10.1042/cs20090536
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous inhibition of TXA2 and PGI2 synthesis increases NO release in mesenteric resistance arteries from cirrhotic rats

Abstract: Our present study examines, in mesenteric resistance arteries, possible vasodilation alterations, and the role of NO and COX (cyclo-oxygenase) derivatives, in cirrhosis. The vasodilator response to acetylcholine was analysed in segments from control and cirrhotic rats. The effects of the non-specific COX inhibitor indomethacin, the specific COX-1 inhibitor SC-560 and the specific COX-2 inhibitor NS-398 were analysed in segments from both groups of rats. NO release was measured, and eNOS [endothelial NOS (NO sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
23
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 29 publications
13
23
1
Order By: Relevance
“…We showed that, in according to the previous studies endothelial vasodilatory response of aortic ring (Clària et al 1994) and SMA (Bolognesi et al 2011;Xavier et al 2010) to acetylcholine is increased in cirrhosis. Also cirrhotic patients displayed an increased endothelium-mediated vasodilation by methacholine, which proposes an amplified synthesis of nitric oxide (Albillos et al 1995).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We showed that, in according to the previous studies endothelial vasodilatory response of aortic ring (Clària et al 1994) and SMA (Bolognesi et al 2011;Xavier et al 2010) to acetylcholine is increased in cirrhosis. Also cirrhotic patients displayed an increased endothelium-mediated vasodilation by methacholine, which proposes an amplified synthesis of nitric oxide (Albillos et al 1995).…”
Section: Discussionsupporting
confidence: 79%
“…In vascular bed, involving those of the mesenteric arteries, the endothelium releases three important vasorelaxator agent; NO, prostacyclin, and endothelial-derived hyperpolarizing factor .However in mesenteric artery, each of these pathways have a role in the vasorelaxation response to acetylcholine (Furchgott et al 1987;Furchgott and Zawadzki 1980) but NO is the principal pathway in these vascular bed because acetylcholine vasorelaxation responses (Harrington et al 2007). It has been shown that endothelium-derived hyperpolarizing factor through activation of K channels (Barriere et al 2000) ,increased myoendothelial gap junctions (Bolognesi et al 2011) and cyclooxygenase/ prostaglandin I 2 system (Graupera et al 2003;Xavier et al 2010) also contributes to the mesenteric vasodilatation elicited by acetylcholine in cirrhotic rats.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, COX inhibition in the inflammatory setting of hypercholesterolemia and chronic ischemia may preferentially inhibit thromboxane production, allowing vasodilatory mechanisms to prevail. This theory is supported by a recent study of a rat model of cirrhosis, where cirrhotic rats demonstrated mesenteric vessel vasodilation in response to both nonselective and selective COX-2 inhibition while noncirrhotic rats did not (27).…”
Section: Discussionsupporting
confidence: 65%
“…Xavier et al (2010) reported that inhibition of TXA 2 and PGI 2 synthesis increased P-eNOS protein, but not eNOS release in mesenteric artery. The detailed mechanism is still unclear; however, ozagrel may activate phosphorylation of eNOS by inhibiting TXA 2 synthase.…”
Section: P-enosmentioning
confidence: 99%